Remedial Practice Beyond Constitutional Text - Leckey, Robert (The American Journal of Comparative Law, 2016)
This Article advances the comparative constitutional literature by examining the exercise of remedial discretion in rights litigation. It compares how the Supreme Court of Canada and the Constitutional Court of South Africa remedy unconstitutional legislation under their respective, relatively new, bills of rights. It uses an internal legal approach and, rejecting universalism and convergence, it pays attention to difference in constitutional texts. By reporting remedial practices and studying the written and unwritten factors that judges identify as conditioning their remedial determinations, the Article studies the significant gap between authoritative text and practice. In a warning for those who draft bills of rights, who rely on their texts to forecast judicial practice, or who simply aim to delineate and understand the exercise of judicial power under bills of rights, judges’ discussion reveals that the scope of action they perceive as legitimate may differ from what a rights instrument’s text implies. This gap has implications for efforts to classify forms of judicial review as strong-form or weak-form, as it may reduce the effective distance between different models as they appear on paper. The Article identifies shifting and contradictory views about reading-in versus invalidating legislation, and about immediate versus delayed orders. Based on its comparison of judicial remedial practices, the Article flags the unavoidable uncertainty of applying a bill of rights to legislation. It interprets the practices of the two countries’ highest courts as embodying a preference for a judicial posture of legislative engagement over one of constitutional enforcement. This conception of the judicial role emerges from similarities in practice, despite differences in the authorizing constitutional texts. The Article establishes a firm basis for normative evaluation of the legitimacy of judicial remedial discretion exercised with a view to engaging the democratic branches of government.